Research on the resilience of Chinese nursing students to workplace vertical violence in clinical practice. (October 2019) - Tian, Lingyun; Zhang, Ying; Li, Xuejiao; Li, Xingxing; Li, Yifang; Ma, Li; Wu, Yuehong; Li, Yinglan
Abstract: This study aimed to explore the status and influencing factors of workplace vertical violence for Chinese nursing students, and examine the relationship between the resilience and workplace vertical violence. Questionnaire survey was conducted with cluster sampling among 486 nursing students by demographic questionnaire, the Resilience Scale of University Students and Questionnaire on Nursing Students' Workplace Vertical Violence. The survey indicated that, 51.23% of nursing students have experienced workplace vertical violence; 64.3% of perpetrators were identified as assigned nurses; 65.46% and 59.44% of nursing students have respectively suffered from adverse psychological and physiological effect; and 66.67% of nursing students determined to work harder and get stronger afterwards. Besides, birthplace, education level, professional identity, sensitive personality, prior knowledge of workplace vertical violence experience before clinical practice, and resilience were the most important influencing factors of workplace vertical violence for Chinese nursing students ( p < 0.05). Workplace vertical violence suffering from nurses is very common for nursing students in the clinical training. Although it has negative impacts on the psychology and physiology of nursing students, more nursing students can positively adjust themselves. Resilience plays a positive role in the nursing students' workplace vertical violence. Highlights: This study indicates that situation of workplace vertical violence suffered by nursing students is not optimistic in China. This study identifies important risk factors of nursing students' workplace vertical violence. Resilience plays a positive role in the nursing students' workplace vertical violence. Most nursing students can positively adjust themselves when they are subjected to workplace vertical violence. This study provides a certain intervention directions for the occurrence of nursing students' workplace vertical violence.